The delicate relation between melanocytes and skin immunity: A game of hide and seek. (7th April 2022) - Speeckaert, Reinhart; Belpaire, Arno; Speeckaert, Marijn; van Geel, Nanja
Abstract: Melanocytes exhibit a complex and intriguing relationship with the skin immune response, leading to several clinical conditions. In some disorders, inappropriate melanocyte destruction (e.g., vitiligo, halo naevi) is problematic, while in others, immune tolerance should be broken (melanoma). Important parts of the dysregulated pathways have been unraveled in pigment disorders, ranging from upregulated interferon (IFN)‐γ signaling to memory T cells, regulatory T cells, and immune checkpoints. Although a network of many factors is involved, targeting key players such as IFN‐γ or checkpoint inhibitors (e.g., programmed death‐ligand 1 (PD‐L1)] can shift the balance and lead to impressive outcomes. In this review, we focus on the immunological mechanisms of the most common inflammatory disorders where the interaction of the immune system with melanocytes plays a crucial role. This can provide new insights into the current state of melanocyte research.